2022
DOI: 10.1002/jlb.4a0421-223rr
|View full text |Cite
|
Sign up to set email alerts
|

Human mucosal Vα7.2+CD161hi T cell distribution at physiologic state and inHelicobacter pyloriinfection

Abstract: Mucosal‐associated invariant T (MAIT) cells are innate‐like, unconventional T cells that are present in peripheral blood and mucosal surfaces. A clear understanding of how MAIT cells in the mucosae function and their role in host immunity is still lacking. Therefore, our aim was to investigate MAIT cell distribution and their characteristics in the gastrointestinal (GI) mucosal tissue based on Vα7.2+CD161hi identification. We showed that Vα7.2+CD161hi T cells are present in both intraepithelial layer and lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…MAIT cells are widely distributed in the human body and are located in the liver, intestine, lungs, blood, skin, and female reproductive mucosa. 6 , 11 , 12 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Nonhuman primates do not have as many MAIT cells as humans, but their distribution in the liver and mucosal tissues is similar to that of humans. 26 The frequency of MAIT cells in commonly used laboratory mice (C57BL/6J and BALB/c) is much lower than in humans.…”
Section: Characteristics Distribution and Activation Of Mucosal-assoc...mentioning
confidence: 99%
“…MAIT cells are widely distributed in the human body and are located in the liver, intestine, lungs, blood, skin, and female reproductive mucosa. 6 , 11 , 12 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Nonhuman primates do not have as many MAIT cells as humans, but their distribution in the liver and mucosal tissues is similar to that of humans. 26 The frequency of MAIT cells in commonly used laboratory mice (C57BL/6J and BALB/c) is much lower than in humans.…”
Section: Characteristics Distribution and Activation Of Mucosal-assoc...mentioning
confidence: 99%
“…MAIT cells are enriched in various types of tissues, accounting for 1%-10% of T cells in peripheral blood [24], 10% in the airway [33,34] and 20%-50% in the liver [24,35]. In stomach, MAIT accounts for about 1%-3% of all T cells in the gastric mucosa, and for the abundance in the gastric antrum is higher than that in the gastric body [36,37]. In the intestinal mucosa, MAIT accounts for up to 10% of αβT cells [24].…”
Section: Phenotypes and Function Of Mait In Digestive Tractmentioning
confidence: 99%
“…In the intestinal mucosa, MAIT accounts for up to 10% of αβT cells [24]. Furthermore, MAIT is highly enriched in the duodenum, but its reactivity towards the MR1-5-OP-RU tetramer is poor [36]. Another work has also shown that up to 25% of the TRAV1-2 + cells in the gastric mucosa cannot respond to the MR1-tetramer [27], addressing the importance of the MR1-tetramer in detecting tissue MAIT cells.…”
Section: Phenotypes and Function Of Mait In Digestive Tractmentioning
confidence: 99%
See 1 more Smart Citation